The Role of Building Information Modeling (BIM) in Enhancing the Environmental and Economic Sustainability of Administrative Buildings in Iraq: The New Central Bank of Iraq as a Case Study (Journal of Engineering, 2025)
With the escalation of environmental challenges and financial constraints worldwide, and the development of the construction industry that has a wide impact on environmental and economic aspects, sustainable design has become increasingly important, especially in developing countries like Iraq. The construction industry has witnessed significant technological advancements in digital tools that enhance sustainability and maintain performance at all stages of project design, management, implementation, and operation. One of the most prominent of these technologies is Building Information Modeling (BIM). This research paper examines the direct role of BIM in enhancing environmental and economic sustainability in administrative building projects, focusing on the Iraqi context and the new Central Bank of Iraq project designed by the famous architect Zaha Hadid. The paper addresses the definition and dimensions of BIM, its development, and its applications in sustainable design. It presents a theoretical framework that explains the role of BIM in reducing emissions and improving resource efficiency, as well as financial and time management. It also addresses the most prominent challenges and opportunities that affect BIM adoption in Iraq, followed by an in-depth study of the environmental and economic strategies of BIM in the Central Bank of Iraq project. The study demonstrates the great potential of BIM in reducing costs, carbon footprint, and energy consumption, which enhances environmental and economic resilience in the long term. The research highlights practical lessons learned and develops a roadmap for the adoption and implementation of BIM on a comprehensive scale, with a special emphasis on administrative building projects.